Platycodin D relieves rheumatoid arthritis by promoting apoptosis of mitochondria to inhibit activation of hedgehog pathway - Peiting Li; Ying Huang; Ju Wang; Jiashun Zeng; Long Li (Taylor & Francis Group, 2023)
Rheumatoid arthritis (RA) displays very similar characteristics to those of tumor cells, platycodin D (PD) is a triterpenoid saponin abundant in Platycodon grandiflorum (PG), plays an important role in the inhibition of tumor growth. Our previous experiments confirmed that PD inhibited MH7A cell proliferation and migration, but it's possible mechanism remain unclear. This study aimed to reveal the mechanism of PD on RA, based on network pharmacology analysis. Rat of CIA was treated with the different doses PD. The arthritis score and paw volume were evaluated, ankle imaging changes were observed via myosseous ultrasound, all rats were anaesthetized by intraperitoneal injection of 25% urethane (1 mL/100 g), and ankle histopathology was observed using hematoxylin and eosin (HE) staining. Cell (MH7A) Counting Kit 8 (CCK8) was used to measure cell activity, and JC-1 assay kit and flow cytometry were employed to examine the cell mitochondrial membrane potential and apoptosis. The expression levels of Sonic hedgehog (Shh) signaling pathway-related proteins were observed by Western blotting. Cell inflammation levels of tumor necrosis factor alpha (TNF-α) and interleukin (IL)-6 being determined via enzyme-linked immunoassay ELISA and q-PCR. In total, the saponin PD significantly improves joint synovium inflammation and apoptosis in CIA rats. The activity of administered MH7A was significantly inhibited, the mitochondrial membrane potential decreased, the expression level of the Shh signaling pathway-related protein SuFu increased, the expression levels of SHh and Gli decreased, and cell serum levels of TNF-a and IL-6 decreased significantly. Therefore, PD exhibits therapeutic potential for synovial hyperplasia in RA.